2007
DOI: 10.1103/physrevlett.99.136803
|View full text |Cite
|
Sign up to set email alerts
|

Doping in Carbon Nanotubes Probed by Raman and Transport Measurements

Abstract: In situ Raman experiments together with transport measurements have been carried out on carbon nanotubes as a function of gate voltage. In metallic tubes, a large increase in the Raman frequency of the G(-) band, accompanied by a substantial decrease of its linewidth, is observed with electron or hole doping. In addition, we see an increase in the Raman frequency of the G(+) band in semiconducting tubes. These results are quantitatively explained using ab initio calculations that take into account effects beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
191
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(204 citation statements)
references
References 26 publications
(49 reference statements)
12
191
0
1
Order By: Relevance
“…Clean, defect-free single-walled carbon nanotubes (SWNTs) are systems which can be used to verify fundamental phenomena such as Wigner crystallization 7 and spin-orbit coupling 8 , and are ideal candidates for testing fundamental physical predictions. In nanotubes, the BO approximation is expected to break down because of the relatively short vibrational period of the longitudinal optical (LO) phonon and the relatively long electronic relaxation time 9,10 . This breakdown has been observed in semiconducting nanotube mats 9 , however, inhomogeneities broaden effects in such systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clean, defect-free single-walled carbon nanotubes (SWNTs) are systems which can be used to verify fundamental phenomena such as Wigner crystallization 7 and spin-orbit coupling 8 , and are ideal candidates for testing fundamental physical predictions. In nanotubes, the BO approximation is expected to break down because of the relatively short vibrational period of the longitudinal optical (LO) phonon and the relatively long electronic relaxation time 9,10 . This breakdown has been observed in semiconducting nanotube mats 9 , however, inhomogeneities broaden effects in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…In nanotubes, the BO approximation is expected to break down because of the relatively short vibrational period of the longitudinal optical (LO) phonon and the relatively long electronic relaxation time 9,10 . This breakdown has been observed in semiconducting nanotube mats 9 , however, inhomogeneities broaden effects in such systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27] Recently, it has been shown that the frequencies and spectral widths of the ⌫ point optical phonons ͑called the G band in Raman spectra͒ depend on the position of the Fermi energy E F and the chirality of the metallic SWNT. [28][29][30][31] The Fermienergy dependence of the Raman spectra can be used to determine the position of the Fermi energy, and the chirality dependence of the Raman spectra provides detailed information on the electronic properties near the Fermi energy of metallic SWNTs. These dependences originate from the fact that the conduction electrons of a metal partly screen the electronic field of the ionic lattice.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved using solid polymer electrolyte (PEO + LiClO 4 ) and Pt wire [17,18,19,20] in top gate geometry where the Fermi level can be significantly shifted by applying small gate voltages (∼ 1V) due to large gate capacitance (∼ 1.5 µF/cm 2 ). The RGO single layer is characterized by 2D Raman band at 2687 cm -1 and temperature coefficient of resistance is ∼ -0.095 % C -1 , same as that of mechanically exfoliated monolayer graphene [21].…”
Section: Introductionmentioning
confidence: 99%